2017
DOI: 10.1007/s00246-017-1757-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for an Elevated Ventricular End-Diastolic Pressure Prior to the Fontan Operation

Abstract: Systemic ventricular end-diastolic pressure (SVEDP) is an important determinant of pulmonary artery pressure in those with a Fontan circulation. Predictors of an elevated SVEDP have been incompletely identified in this population. All who underwent the Fontan operation at our center between 1/2009 and 12/2013 were retrospectively identified. SVEDP at the pre-Fontan catheterization and other patient variables were extracted. We identified 61 patients. Pre-Fontan SVEDP was positively associated with systemic ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“… 28 , 29 , 30 The chronic preload insufficiency may result in myocardial remodelling, increased ventricular stiffness, increased filling pressures and eventually a progressive decline in cardiac output. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ,…”
Section: Terms and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 , 29 , 30 The chronic preload insufficiency may result in myocardial remodelling, increased ventricular stiffness, increased filling pressures and eventually a progressive decline in cardiac output. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ,…”
Section: Terms and Definitionsmentioning
confidence: 99%
“… 37 , 38 At the moment, direct measurement of ventricular end‐diastolic pressure remains the gold standard for the evaluation of diastolic dysfunction. 39 , 40 Various studies have suggested >10 or 12 mmHg as defining an elevated end‐diastolic pressure, with the recent emergence of the potential role for provocative testing (fluid challenge) to help identify patients with occult diastolic dysfunction. 39 , 40 , 41 Data on the haemodynamic definition, however, are sparse, and further research is needed to provide more definitive guidance on specific cut‐offs and best options for provocative testing.…”
Section: Terms and Definitionsmentioning
confidence: 99%
“…In prior work, we have shown that patients with systemic right ventricle have a higher single ventricle end-diastolic pressure before the bidirectional Glenn operation and before the Fontan operation compared to those with LV. 13,14 We hypothesise that chronic preload deprivation in the Fontan circulation drives diastolic dysfunction regardless of ventricular morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its importance, diastolic function of the palliated single ventricle is poorly understood, and no-invasive risk factors associated with higher end-diastolic ventricular pressure have not yet been clearly identified in pre-Fontan patients. In 2018, Schwartz et al 23 studied possible predictors of an elevated end-diastolic ventricular pressure in pre-Fontan patients, and they found that invasive ventricular systolic pressure and decreased ventricular systolic function were positively associated with end-diastolic ventricular pressure. In our knowledge, this is the first study that investigates non-invasive MRI predictors of pre-Fontan end-diastolic ventricular pressure.…”
Section: Discussionmentioning
confidence: 99%